The Effects of Profitability, Liquidity and Company Growth on Going Concern Audit Opinion - Nastiti Rizky Shiyammurti (ProBisnis : Jurnal Manajemen, 2023)
This research was conducted on manufacturing companies listed on the IDX in 2019. The purpose of this study was to see the effect of Profitability, Liquidity and Company Growth on Going Concern Audit Opinions. The purpose of this study is to determine the effect of profitability, liquidity and company growth on the Going Concern audit opinion of manufacturing companies listed on the IDX in 2019 . The population in this research is manufacturing companies listed on the IDX in 2019, with a sample of 32 companies. The type of research data used is secondary data. Sampling technique using purposive sampling method. The research design uses descriptive and associative methods. The results of the (partial) influence calculation can be seen from the results of the -2 Log likelihood value of 14.412 with the Cox&Snell R Square value of 0.341 (34.1%) and the value of Negelkerke R Square of 0.588 (58.8%). This means that the independent variables namely Profitability, Liquidity and Company Growth are able to explain the variation of the dependent variable namely Going Concern Audit Opinion of 58.8% while the rest is explained by other factors outside this study.  The research results can be seen from the results of the chi-square value of 13.326 with a df of 3 and significance has a probability value of 0.004 which is smaller than 0.05 so that hypothesis 3 is accepted. It can be concluded that Profitability, Liquidity and Company Growth have a negative effect simultaneously on the Going Concern Audit Opinion.